Digitization and Community Participation - Martina Pocchiari; Jason M.T. Roos (CESifo GmbH, 2025)
Digitization technologies reshape the way people engage in social and business activities, transitioning events from in-person to virtual formats. However, existing evidence on the effects of digitization on participation remains fragmented and contradictory. The authors address this gap by analyzing data describing 645,013 events organized in 2024 by 12,105 diverse communities comprising 493,143 individuals. Leveraging the structure, granularity, and attributes of the data, which include large amounts of unstructured text, the study finds that digitization has, on average, positive effects on participation. These effects, however, are highly heterogeneous, depending on group interests, event features, and even time. For example, digitization negatively affects participation in highly specialized and technical events, especially those emphasizing skill development in the areas of technology and business. Digitization effects fluctuate significantly over the year for certain types of events and groups, occasionally changing sign throughout 2024. The results reconcile some of the contradictory evidence on digitization effects and highlight potential gaps between the supply of digitized events and participants' preferences. The study also identifies key opportunities for businesses and policy-makers driving digital transformation, emphasizing that delivering specialized knowledge and supporting physical tasks represent the most impactful avenues for the digitization of future events.
Keywords: M31; O33; 330; Digitization; Community engagement; Natural language processing; Heterogeneity